PEER INFLUENCE FACTORS ON FREE SEXUAL BEHAVIOR AMONG ADOLESCENTS IN STATE SENIOR HIGH SCHOOL 2, ENREKANG DISTRICT - Chintya Najwa Ananta Suaib; Makhrajani Majid; Rini Anggraeny; Sukmawati Thasim; Rasidah Wahyuni Sari (Universitas Muhammadiyah Ponorogo, 2026)
Sexual behavior among adolescents is a growing trend, especially in the school environment. Adolescents are generally known to have strong curiosity and the process of searching for identity, if not accompanied by adequate guidance and understanding, has the potential to lead to deviant behavior. This study aims to analyze the influence of peers on promiscuous sexual behavior among adolescents at SMA Negeri 2, Enrekang Regency. The type of research used is quantitative with a cross-sectional design. The study sample consisted of 249 students in grades X and XI, selected through proportional random sampling. Data were collected using a closed questionnaire and analyzed using the chi-square test. The results of the analysis showed that the majority of respondents had low sexual behavior compliance, namely 65.9%. Peer factors were proven to have a significant relationship with promiscuous sexual behavior (p = 0.010). These findings indicate that peer influence is a dominant factor in adolescent sexual behavior. It is recommended that adolescents need to increase awareness and be selective in choosing friends.